Nursing of a patient with post-stroke diarrhea treated by Ji’s Traditional Chinese Medicine Tuina (吉氏中医推拿治疗1例中风后腹泻患者的护理体会) - LIU Yanna (刘燕娜); WANG Xuesong (王雪送); GAO Yanbin (高燕斌); FAN Yan (范艳); TANG Ling (唐玲); HU Shirong (胡世荣) (中西医结合护理)
This paper summarized the nursing management for a patient with post-stroke diarrhea treated by Ji’s Traditional Chinese Medicine Tuina. Based on the syndrome differentiation, the Ji’s Traditional Chinese Medicine Tuina therapy was carried out in combination with dietary management, emotional care and basic nursing, in order to relieve the symptoms of diarrhea. (本文总结运用吉氏中医推拿治疗1例中风后腹泻患者的护理体验。基于中医辨证, 采取吉氏中医推拿法治疗腹泻, 同时配合饮食调护、情志护理和一般护理, 能有效改善腹泻症状。)